2013
DOI: 10.2308/iace-50441
|View full text |Cite
|
Sign up to set email alerts
|

Online Homework Managers and Intelligent Tutoring Systems: A Study of Their Impact on Student Learning in the Introductory Financial Accounting Classroom

Abstract: The online homework manager (OHM) and the intelligent tutoring system (ITS) are two supplemental teaching tools available for accounting educators' use in the introductory financial accounting course. While research related to these systems is limited, prior studies find a tenuous performance advantage related to their use. To advance the literature in this area, this paper evaluates the performance benefit related to an OHM and an ITS, each employed independently as an additional study aid during the first co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…Incorporating an OHM into the classroom has been shown to provide many benefits for student learning (Gaffney et al, 2010;Phillips and Johnson, 2011) even though there are some challenges (Du, 2011;Hahn et al, 2013;Khanlarian and Singh, 2014). Accordingly, the OHM was used in the flipped classroom as a supporting learning strategy, as opposed to a supplantive strategy.…”
Section: Ohmmentioning
confidence: 99%
“…Incorporating an OHM into the classroom has been shown to provide many benefits for student learning (Gaffney et al, 2010;Phillips and Johnson, 2011) even though there are some challenges (Du, 2011;Hahn et al, 2013;Khanlarian and Singh, 2014). Accordingly, the OHM was used in the flipped classroom as a supporting learning strategy, as opposed to a supplantive strategy.…”
Section: Ohmmentioning
confidence: 99%
“…Introducing CMAs into Online Financial Accounting Course 6 (2014) suggested that students who submitted their homework using pen and paper, gained better scores than students who were tested online. Hahn, Fairchild and Dowis (2013) reported no advantages in relation to the use of an online homework management system on an introductory Financial Accounting course. The system incorporated a facility for online testing, compared to more conventional paper methods, but no differences were observed on the final examination performance across the experimental and control groups.…”
Section: Drawing On Evidence From An Intermediate Accounting Course mentioning
confidence: 98%
“…                                                            20       (Morgan, 2013;Hahn, Fairchild, & Dowis, 2013…”
Section:                    unclassified